2008
DOI: 10.1002/ijc.23806
|View full text |Cite
|
Sign up to set email alerts
|

KAI1/CD82 is a novel target of estrogen receptor‐mediated gene repression and downregulated in primary human breast cancer

Abstract: The cell-surface glycoprotein KAI1 suppresses tumor growth and metastasis in various animal models. Downregulation of KAI1 has been implicated in the progression of cancer. However, the mechanisms of KAI1 inactivation are poorly understood. This is the first study that investigates expression and regulation of KAI1 in human breast cancer. KAI1 expression was analyzed on custommade tissue microarrays comprising 209 well-characterized breast cancers and normal mammary gland tissue. Strong KAI1 immunoreactivity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 33 publications
0
56
0
Order By: Relevance
“…Increasing attention has been paid to the interaction between different factors involved in metastatic processes in hormone-sensitive tumors [22][23][24]. To our knowledge, this is the first study which has analyzed the association between steroid receptors, KAI1 protein, MMP-2, and MMP-9 -as well as between KAI1, MMP-2, and MMP-9 Table 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing attention has been paid to the interaction between different factors involved in metastatic processes in hormone-sensitive tumors [22][23][24]. To our knowledge, this is the first study which has analyzed the association between steroid receptors, KAI1 protein, MMP-2, and MMP-9 -as well as between KAI1, MMP-2, and MMP-9 Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Correlations between examined biomarkers in endometrial cancers www.fhc.viamedica.pl -in endometrial cancer. Earlier studies revealed that KAI1 protein may cooperate with MMPs, and displays a different role in its functions in ER-negative and ER-positive breast cancers [14,22,23]. Christgen et al [22,23] found that in ER-positive breast cancers the KAI1 protein was downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…All specimens were made anonymous for scientific purposes and were compiled on tissue microarrays for immunohistochemical assessment of nuclear p53 accumulation as described previously. 41 Clinicopathological characteristics are reported in Supplementary Table 1.…”
Section: Tumor Specimensmentioning
confidence: 99%
“…1 However, it is not appropriate to dismiss our approaches, methods, and findings as a ''replication of portions of a paper'' published by Huang et al 2 In addition, several results of our study are not cited correctly by Dr. Geradts:…”
Section: Dear Sirmentioning
confidence: 85%